Functional coefficient quantile regression model with time-varying loadings - Alev Atak; Gabriel Montes-Rojas; Jose Olmo (Journal of Applied Economics, 2023)
This paper proposes a functional coefficient quantile regression model with heterogeneous and time-varying regression coefficients and factor loadings. Estimation of the model coefficients is done in two stages. First, we estimate the unobserved common factors from a linear factor model with exogenous covariates. Second, we plug-in an affine transformation of the estimated common factors to obtain the functional coefficient quantile regression model. The quantile parameter estimators are consistent and asymptotically normal. The application of this model to the quantile process of a cross-section of U.S. firms' excess returns confirms the predictive ability of firm-specific covariates and the good performance of the local estimator of the heterogeneous and time-varying quantile coefficients.
Keywords: 330; panel data; partially linear regression model; Quantile factor model; time-varying factor loadings